Carpal tunnel syndrome and manual milking: nerve conduction studies in 43 cases Síndrome do túnel do carpo e ordenha: estudo de condução nervosa em 43 casos - João Aris Kouyoumdjian; Rogério Gayer Machado de Araújo (Arquivos de Neuro-Psiquiatria)
From 1989 to 2004, 3125 consecutive patients had electrodiagnosis of carpal tunnel syndrome (CTS); from these 43 cases (1.38%) were associated to manual milking; mean age was 44.9 years and 88.4% were male. The mean time in the milking profession was 247 months; the mean daily milking time was 146 minutes; symptoms referred at electrodiagnostic consultation had lasted on average 34 months, 83% were bilateral. The median sensory nerve conduction study was abnormal in 75.6% to the right and 66.7% to the left hand. The median nerve motor distal latency (MDL) was abnormal in 92.1% to the right and in 80.0% to the left hand. There were no differences between right and left for all electrophysiological parameters. In CTS related to manual milking most cases were men, with the MDL more affected than the sensory distal latencies and the electrophysiological abnormalities were found to be symmetric. Manual milking could be a natural model for occupational CTS. In contrast to idiopathic CTS, there was a greater involvement of motor fascicles; this finding is remarkable for CTS. No período de 1989 a 2004 foram diagnosticados por meio de eletroneuromiografia 3125 casos consecutivos de Síndrome do túnel do carpo (STC) e destes, 43 (1,38%) estavam associados com ordenha; a média de idade foi 44,9 anos e 88,4% eram do sexo masculino. O tempo médio de atividade profissional era 247 meses; o tempo médio de ordenha diária era 146 minutos; a sintomatologia referida na consulta eletrodiagnóstica tinha em média 34 meses de duração e 83% a referiam bilateralmente. O estudo da condução senstiva do nervo mediano estava anormal em 75,6% na mão direita e em 66,7% da mão esquerda. A latência distal motora (LDM) do nervo mediano estava anormal em 92,1% à direita e em 80% à esquerda. Não havia diferença significante dos parâmetros eletrofisiológicos entre os lados direito e esquerdo. Na STC associada a ordenha, a maioria dos casos é de homens, a LDM está mais afetada que as latências distais sensitivas e as anormalidades eletrofisiológicas são simétricas. A ordenha poderia ser considerada um modelo para STC ocupacional e diferente da STC idiopática, há maior envolvimento dos fascículos motores.